Microbial self-repairing crack concrete and preparation method thereof

CN122647183APending Publication Date: 2026-08-28TONGLU BENTENG BUILDING MATERIALS PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610811377.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

(1)现有技术中,混凝土裂缝修复多采用表面涂覆、压力灌浆、填缝密封和外加修补材料等方式进行处理,上述方式通常需要人工巡检和外部施工,难以及时修复结构内部或隐蔽部位的微裂缝,并且修补材料与原混凝土基体之间容易存在界面粘结不足、收缩不一致和耐久性不匹配等问题

Benefits of technology

(1)利用轻质多孔载体负载巴氏芽孢杆菌,并通过真空浸渍提高巴氏芽孢杆菌进入轻质多孔载体孔隙的数量,使微生物在混凝土内部形成稳定储存单元,实现裂缝进水后菌体逐步释放并诱导碳酸钙沉积的技术效果,解决现有混凝土裂缝修复过程中微生物难以在强碱环境和拌合剪切条件下长期存活的技术问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122647183A_ABST
    Figure CN122647183A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of building material self-repairing concrete, and discloses a kind of microbial self-repairing crack concrete and a preparation method thereof, which comprises the following raw materials by weight: cement 350-370 parts, fly ash 55-70 parts, mineral powder 35-45 parts, fine aggregate 670-690 parts, coarse aggregate 1070-1090 parts, water 150-160 parts, water reducing agent 4.5-5.5 parts, microbial mineralization repair particles 22-34 parts and nutrient slow-release particles 14-22 parts. By loading Bacillus pasteurii on a light and porous carrier, and using sodium alginate and calcium chloride to cross-link and form a gel coating layer, microbial mineralization repair particles are prepared. At the same time, by using calcium lactate, urea and sodium silicate, nutrient slow-release particles are prepared. When cracks occur in the concrete and water enters, the microbial mineralization repair particles gradually release bacterial bodies, and the nutrient slow-release particles continuously release calcium sources and urea, so that Bacillus pasteurii induces the formation of calcium carbonate deposits and blocks the cracks, thereby improving the survival rate of bacterial bodies and the duration of repair, and improving the crack repair rate, the compressive strength recovery rate of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of self-healing concrete technology in building materials, and particularly relates to a microbial self-healing crack concrete and its preparation method. Background Technology

[0002] Concrete, a commonly used foundation building material in roads, bridges, tunnels, hydraulic structures, and underground engineering, is susceptible to microcracks during long-term service due to factors such as load, temperature and humidity changes, freeze-thaw cycles, wet-dry cycles, and shrinkage deformation. Once cracks form, external moisture, chloride ions, sulfate ions, and carbon dioxide can easily penetrate the concrete interior along the cracks, causing steel corrosion, matrix deterioration, and reduced durability, thereby shortening the service life of the concrete structure. Therefore, it is necessary to provide a microbial self-healing crack concrete and its preparation method, enabling the concrete to form mineral deposits in the crack area after cracks appear and come into contact with moisture, achieving self-sealing of cracks, restoration of impermeability, and improvement of durability.

[0003] The following issues need to be addressed in the existing technology: (1) In the existing technology, concrete crack repair is mostly carried out by surface coating, pressure grouting, crack sealing and external repair materials. The above methods usually require manual inspection and external construction, which makes it difficult to repair micro-cracks inside the structure or in hidden parts in a timely manner. In addition, there are problems such as insufficient interfacial bonding, inconsistent shrinkage and mismatch of durability between the repair materials and the original concrete matrix. Therefore, the existing concrete crack repair methods have the problems of delayed repair, insufficient repair depth and unstable long-term sealing effect.

[0004] (2) In the prior art, some microbial self-healing concretes achieve calcium carbonate deposition by directly incorporating microorganisms, calcium sources, and urea. However, the shearing action during concrete mixing, the strong alkaline environment after hardening, and changes in pore water can easily reduce the survival rate of microorganisms. Microorganisms and nutrients are also prone to premature release, resulting in insufficient effective microorganisms and mineralized substrates after crack formation. At the same time, a single microbial carrier system is difficult to balance microbial protection, slow nutrient release, and mechanical property maintenance, which can easily lead to problems such as insufficient crack repair rate, low compressive strength recovery rate, and decreased freeze-thaw durability. Summary of the Invention

[0005] To address the above issues and overcome the shortcomings of existing technologies, this invention provides a microbial self-healing crack concrete and its preparation method. It involves loading Bacillus pasteurellii onto a lightweight porous carrier and using sodium alginate and calcium chloride to crosslink and form a gel coating layer, thus preparing microbial mineralization repair particles. Simultaneously, nutrient-releasing particles are prepared using calcium lactate, urea, and sodium silicate. When cracks appear in the concrete and moisture enters, the microbial mineralization repair particles gradually release bacteria, while the nutrient-releasing particles continuously release calcium and urea, inducing Bacillus pasteurellii to form calcium carbonate deposits that seal the cracks. This process improves the survival rate of the bacteria and the sustainability of the repair, thereby improving the concrete crack repair rate, compressive strength recovery rate, impermeability, and freeze-thaw durability.

[0006] To address the above issues, this invention provides a microbial self-healing crack concrete and its preparation method. It utilizes a lightweight porous carrier loaded with urease-producing microorganisms and a gel coating layer formed by cross-linking sodium alginate and calcium chloride to prepare microbial mineralization repair particles. Simultaneously, it prepares nutrient-release particles using calcium lactate, urea, sodium silicate, sodium alginate, and calcium chloride. When the microbial mineralization repair particles and nutrient-release particles are incorporated into the concrete mixture, and when cracks appear and moisture enters, these particles gradually release bacteria, calcium sources, and urea, causing calcium carbonate deposits to form in the crack area. This achieves crack sealing, recovery of compressive strength, improvement of impermeability, and enhancement of freeze-thaw durability, solving the problems of existing concrete crack repairs relying on external repairs, insufficient repair depth, poor repair durability, and easy water seepage and deterioration at crack sites.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: This invention provides a microbial self-healing crack concrete, which comprises the following raw materials in parts by weight: 350-370 parts cement, 55-70 parts fly ash, 35-45 parts mineral powder, 670-690 parts fine aggregate, 1070-1090 parts coarse aggregate, 150-160 parts water, 4.5-5.5 parts water-reducing agent, 22-34 parts microbial mineralization repair particles, and 14-22 parts nutrient slow-release particles.

[0008] Furthermore, the microbial mineralization remediation particles comprise the following raw materials in parts by weight: 18-22 parts of lightweight porous carrier, 30-40 parts of Bacillus pasteurellium bacterial solution, 1.6-2.4 parts of sodium alginate, 2.5-3.5 parts of calcium chloride, and 1.2-1.8 parts of protective agent.

[0009] Furthermore, the protective agent is made by mixing trehalose and skim milk powder in a mass ratio of 1:1.

[0010] Furthermore, the nutrient slow-release granules comprise the following raw materials in parts by weight: 22-28 parts calcium lactate, 10-14 parts urea, 3-5 parts sodium silicate, 1.5-2.1 parts sodium alginate, and 2.0-3.0 parts calcium chloride.

[0011] Furthermore, the cement is P.O42.5 ordinary Portland cement; the fly ash is Grade II fly ash; the mineral powder is S95 grade granulated blast furnace slag powder; the fine aggregate is river sand with a fineness modulus of 2.6; the coarse aggregate is continuously graded crushed stone with a particle size of 5-20mm; and the water-reducing agent is polycarboxylate high-efficiency water-reducing agent with a water reduction rate ≥25%.

[0012] Furthermore, the lightweight porous carrier is one of expanded perlite, zeolite powder, and ceramsite powder; the concentration of the Bacillus pasteurellium bacterial solution is... The calcium source is one of calcium lactate, calcium acetate, and calcium nitrate.

[0013] This invention also provides a method for preparing microbial self-healing cracked concrete, specifically including the following steps: Step 1: Weigh and dry the lightweight porous carrier, cool it to room temperature, place it in a vacuum impregnation tank, add Pasteurella multocida bacterial solution and protectant, remove the vacuum after vacuum impregnation and let it stand, so that Pasteurella multocida enters the pores of the lightweight porous carrier to obtain bacteria-loaded porous particles. Step 2: Weigh sodium alginate and add it to deionized water and stir to dissolve it to obtain sodium alginate solution; add the bacteria-loaded porous particles to the sodium alginate solution for rolling coating, then add them dropwise to calcium chloride solution for cross-linking, filter and dry at low temperature to obtain microbial mineralization repair particles; Step 3: Weigh calcium lactate, urea and sodium silicate, mix them evenly, add them to sodium alginate solution to granulate, then place them in calcium chloride solution for cross-linking, filter and dry to obtain nutrient slow-release granules; Step 4: Weigh out cement, fly ash, mineral powder, fine aggregate and coarse aggregate and add them to a concrete mixer to dry mix and obtain a dry-mixed aggregate system; Step 5: Mix water and water-reducing agent and then add to the dry aggregate system and stir to obtain the basic concrete mixture; Step 6: Add the microbial mineralization repair particles and nutrient slow-release particles to the base concrete mixture and stir at low speed to evenly disperse the microbial mineralization repair particles and nutrient slow-release particles, thus obtaining a microbial self-healing crack concrete mixture. Step 7: Pour the microbial self-healing crack concrete mixture into the mold, vibrate it, smooth the surface, cover it with a film, demold it, and cure it according to standard to obtain microbial self-healing crack concrete.

[0014] Further, in step 1, the drying temperature of the lightweight porous carrier is 105℃ and the drying time is 4h; the vacuum degree of the vacuum impregnation is -0.075MPa to -0.085MPa, the vacuum impregnation time is 25-40min, and the standing time after the vacuum is released is 50-70min.

[0015] Furthermore, in step 2, the rolling coating time is 18-25 min, the crosslinking time is 25-35 min, the low-temperature drying temperature is 30°C, and the low-temperature drying time is 6-7 h.

[0016] Furthermore, in step 3, the crosslinking time is 35-45 min, the drying temperature is 35℃, and the drying time is 8-9 h.

[0017] Further, in step 4, the dry mixing time is 90-100s; in step 5, the stirring time is 120-130s; and in step 6, the low-speed stirring time is 80-100s.

[0018] Furthermore, in step 7, the compaction time is 60-70 seconds, the demolding time is 24 hours, the standard curing temperature is 20°C, the relative humidity is 95%, and the standard curing time is 28 days.

[0019] The beneficial effects of this invention are as follows: (1) By using a lightweight porous carrier to load Bacillus pasteurellii and increasing the number of Bacillus pasteurellii entering the pores of the lightweight porous carrier through vacuum impregnation, the microorganisms form a stable storage unit inside the concrete, thereby achieving the technical effect of gradually releasing the bacteria and inducing calcium carbonate deposition after water enters the crack, thus solving the technical problem that microorganisms are difficult to survive for a long time in a strong alkaline environment and under mixing and shearing conditions during the existing concrete crack repair process.

[0020] (2) By using sodium alginate and calcium chloride to cross-link and form a gel coating layer to coat the bacteria-laden porous particles, it can protect Bacillus pasteurellii during the mixing, hardening and service stages of concrete, and release it in response after water enters the crack, thereby achieving the technical effects of improving the survival rate of bacteria, extending the repair duration and improving the crack repair rate, and solving the technical problems of premature release of bacteria, insufficient effective bacteria in the later stage and poor crack repair durability in the existing microbial repair system.

[0021] (3) Nutrient slow-release particles are prepared by using calcium lactate, urea and sodium silicate to continuously provide calcium source, urea and mineralization auxiliary components to the crack area. Bacillus pasteurellii promotes the decomposition of urea and generates carbonate ions through the action of urease. The carbonate ions combine with calcium ions to form calcium carbonate deposits, thereby achieving the technical effects of crack sealing, compressive strength restoration, impermeability improvement and freeze-thaw durability improvement. This solves the technical problems of insufficient mineralization substrate supply, low crack closure degree and difficulty in long-term sealing of seepage channels in the existing concrete crack repair process. Attached Figure Description

[0022] The accompanying drawings are provided to further understand the present invention and form part of the specification. They are used together with the embodiments of the present invention to explain the invention and do not constitute a limitation thereof.

[0023] Figure 1 This is a flowchart illustrating the preparation process of microbial self-healing crack concrete proposed in this invention. Figure 2 This is a schematic diagram of the self-healing mechanism of microbial self-healing cracked concrete proposed in this invention; Figure 3 The crack repair rate test results are for the microbial self-healing cracked concrete prepared in Examples 1-4 and Comparative Examples 1-4. Figure 4 The results of freeze-thaw cycle performance studies of the microbial self-healing crack concrete prepared in Examples 1-4 and Comparative Examples 1-4 are presented. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention. The preferred embodiments and materials described herein are for illustrative purposes only and do not limit the scope of this application.

[0026] Unless otherwise specified, all methods described in the following examples and comparative examples are conventional, and all parts are by weight. Unless otherwise specified, all materials used in the following examples are new materials purchased from the market. Specifically, the cement used is P.O42.5 ordinary Portland cement; the fly ash used is Grade II fly ash; the mineral powder used is S95 grade granulated blast furnace slag powder; the fine aggregate used is river sand with a fineness modulus of 2.6; the coarse aggregate used is continuously graded crushed stone with a particle size of 5-20 mm; the water-reducing agent used is polycarboxylate superplasticizer with a water reduction rate ≥25%; the lightweight porous carrier used is one of expanded perlite, zeolite powder, and ceramsite powder; and the urease-producing microorganism used is Bacillus pasteurellii with a bacterial concentration of [missing information]. The calcium source used is one of calcium lactate, calcium acetate, and calcium nitrate; the coating agent used is a gel coating system formed by cross-linking sodium alginate and calcium chloride.

[0027] Example 1: This example provides a microbial self-healing crack concrete, which includes the following raw materials by weight: 360 parts cement, 60 parts fly ash, 40 parts mineral powder, 680 parts fine aggregate, 1080 parts coarse aggregate, 155 parts water, 5.0 parts water-reducing agent, 28 parts microbial mineralization repair particles, and 18 parts nutrient slow-release particles. The microbial mineralization repair particles comprise the following raw materials in parts by weight: 20 parts of lightweight porous carrier, 35 parts of Bacillus pasteurellium bacterial solution, 2.0 parts of sodium alginate, 3.0 parts of calcium chloride, and 1.5 parts of protective agent; the protective agent is prepared by mixing trehalose and skim milk powder in a mass ratio of 1:1. The sustained-release nutrient granules comprise the following raw materials in parts by weight: 25 parts calcium lactate, 12 parts urea, 4 parts sodium silicate, 1.8 parts sodium alginate, and 2.5 parts calcium chloride; The preparation method of the microbial self-healing crack concrete is as follows: Step 1: Weigh 20 parts of lightweight porous carrier, dry at 105℃ for 4 hours, cool to room temperature and place in a vacuum impregnation tank, add 35 parts of Pasteurella multocida bacterial solution and 1.5 parts of protectant, impregnate under a vacuum of -0.08MPa for 30 minutes, release the vacuum and let stand for 60 minutes to allow Pasteurella multocida to enter the pores of the lightweight porous carrier, and obtain bacteria-loaded porous particles; Step 2: Weigh 2.0 parts of sodium alginate and add it to deionized water and stir to dissolve, so as to obtain sodium alginate solution; add the bacteria-loaded porous particles to the sodium alginate solution and roll to coat for 20 min, then add them dropwise to a calcium chloride solution prepared with 3.0 parts of calcium chloride for cross-linking for 30 min, filter and dry at low temperature at 30℃ for 6 h to obtain microbial mineralization repair particles. Step 3: Weigh 25 parts of calcium lactate, 12 parts of urea and 4 parts of sodium silicate and mix them evenly. Add them to a sodium alginate solution prepared with 1.8 parts of sodium alginate to granulate. Then place them in a calcium chloride solution prepared with 2.5 parts of calcium chloride for crosslinking for 40 minutes. After filtration, dry them at 35°C for 8 hours to obtain nutrient slow-release granules. Step 4: Weigh 360 parts of cement, 60 parts of fly ash, 40 parts of mineral powder, 680 parts of fine aggregate and 1080 parts of coarse aggregate and add them to the concrete mixer. Dry mix for 90 seconds to obtain a dry-mixed aggregate system. Step 5: Mix 155 parts water and 5.0 parts water-reducing agent and add them to the dry aggregate system. Stir for 120 seconds to obtain the basic concrete mixture. Step 6: Add 28 parts of microbial mineralization repair particles and 18 parts of nutrient slow-release particles to the base concrete mixture, and stir at low speed for 90 seconds to make the microbial mineralization repair particles and nutrient slow-release particles evenly dispersed, and obtain microbial self-healing crack concrete mixture. Step 7: Pour the microbial self-healing crack concrete mixture into the mold, vibrate it for 60 seconds, smooth the surface, cover it with a film, remove it from the mold after 24 hours, and place it in a standard curing environment of 20℃ and 95% relative humidity for 28 days to obtain microbial self-healing crack concrete.

[0028] Regarding parameter adjustments: In step 1, the vacuum impregnation time is used to adjust the loading of Bacillus pasteurellii in the lightweight porous carrier. When the vacuum impregnation time is less than 20 minutes, the number of Bacillus pasteurellii entering the pores of the lightweight porous carrier is insufficient; when the vacuum impregnation time is greater than 45 minutes, the moisture content of the bacteria-loaded porous particles is too high, resulting in decreased uniformity of subsequent coating. In step 2, the addition of sodium alginate and calcium chloride is used to adjust the thickness of the outer gel film of the microbial mineralization repair particles. When the gel film thickness is insufficient, it is easy to cause damage to the bacteria during the concrete mixing stage; when the gel film thickness is too large, the release rate of nutrients and bacteria after water enters the cracks decreases.

[0029] Example 2: This example provides a microbial self-healing crack concrete, which includes the following raw materials by weight: 350 parts cement, 70 parts fly ash, 35 parts mineral powder, 690 parts fine aggregate, 1070 parts coarse aggregate, 150 parts water, 4.5 parts water-reducing agent, 22 parts microbial mineralization repair particles, and 14 parts nutrient slow-release particles. The microbial mineralization remediation particles comprise the following raw materials in parts by weight: 18 parts of lightweight porous carrier, 30 parts of Bacillus pasteurellium bacterial solution, 1.6 parts of sodium alginate, 2.5 parts of calcium chloride, and 1.2 parts of protective agent; The sustained-release nutrient granules comprise the following raw materials in parts by weight: 22 parts calcium lactate, 10 parts urea, 3 parts sodium silicate, 1.5 parts sodium alginate, and 2.0 parts calcium chloride; The preparation method of the microbial self-healing crack concrete is as follows: Step 1: Weigh 18 parts of lightweight porous carrier, dry at 105℃ for 4 hours, cool to room temperature and place in a vacuum impregnation tank, add 30 parts of Bacillus pasteurellium bacterial solution and 1.2 parts of protectant, impregnate at -0.075MPa vacuum for 25 minutes, release the vacuum and let stand for 50 minutes to obtain bacteria-loaded porous particles. Step 2: Weigh 1.6 parts of sodium alginate and add it to deionized water and stir to dissolve, so as to obtain sodium alginate solution; add the bacteria-loaded porous particles to the sodium alginate solution and roll to coat for 18 min, then add them dropwise to a calcium chloride solution prepared with 2.5 parts of calcium chloride for cross-linking for 25 min, filter and dry at low temperature at 30℃ for 6 h to obtain microbial mineralization repair particles. Step 3: Weigh 22 parts of calcium lactate, 10 parts of urea and 3 parts of sodium silicate and mix them evenly. Add them to a sodium alginate solution prepared with 1.5 parts of sodium alginate to granulate. Then place them in a calcium chloride solution prepared with 2.0 parts of calcium chloride for crosslinking for 35 minutes. After filtration, dry them at 35°C for 8 hours to obtain nutrient slow-release granules. Step 4: Weigh 350 parts of cement, 70 parts of fly ash, 35 parts of mineral powder, 690 parts of fine aggregate and 1070 parts of coarse aggregate and add them to the concrete mixer. Dry mix for 90 seconds to obtain a dry-mixed aggregate system. Step 5: Mix 150 parts water and 4.5 parts water-reducing agent and add them to the dry aggregate system. Stir for 120 seconds to obtain the basic concrete mixture. Step 6: Add 22 parts of microbial mineralization repair particles and 14 parts of nutrient slow-release particles to the base concrete mixture and stir at low speed for 80 seconds to obtain microbial self-healing crack concrete mixture. Step 7: Pour the microbial self-healing crack concrete mixture into the mold, vibrate it for 60 seconds, smooth the surface, cover it with a film, remove it from the mold after 24 hours, and place it in a standard curing environment of 20℃ and 95% relative humidity for 28 days to obtain microbial self-healing crack concrete.

[0030] Example 3: This example provides a microbial self-healing crack concrete, which includes the following raw materials by weight: 370 parts cement, 55 parts fly ash, 45 parts mineral powder, 670 parts fine aggregate, 1090 parts coarse aggregate, 160 parts water, 5.5 parts water-reducing agent, 34 parts microbial mineralization repair particles, and 22 parts nutrient slow-release particles. The microbial mineralization remediation particles comprise the following raw materials in parts by weight: 22 parts of lightweight porous carrier, 40 parts of Bacillus pasteurellium bacterial solution, 2.4 parts of sodium alginate, 3.5 parts of calcium chloride, and 1.8 parts of protective agent; The sustained-release nutrient granules comprise the following raw materials in parts by weight: 28 parts calcium lactate, 14 parts urea, 5 parts sodium silicate, 2.1 parts sodium alginate, and 3.0 parts calcium chloride; The preparation method of the microbial self-healing crack concrete is as follows: Step 1: Weigh 22 parts of lightweight porous carrier, dry at 105℃ for 4 hours, cool to room temperature and place in a vacuum impregnation tank, add 40 parts of Pasteurella multocida bacterial solution and 1.8 parts of protectant, impregnate under a vacuum of -0.085MPa for 40 minutes, release the vacuum and let stand for 70 minutes to allow Pasteurella multocida to enter the pores of the lightweight porous carrier and obtain bacteria-loaded porous particles; Step 2: Weigh 2.4 parts of sodium alginate and add it to deionized water and stir to dissolve, so as to obtain sodium alginate solution; add the bacteria-loaded porous particles to the sodium alginate solution and roll to coat for 25 min, then add it dropwise to a calcium chloride solution prepared with 3.5 parts of calcium chloride for cross-linking for 35 min, filter and dry at low temperature at 30℃ for 7 h to obtain microbial mineralization repair particles. Step 3: Weigh 28 parts of calcium lactate, 14 parts of urea and 5 parts of sodium silicate and mix them evenly. Add them to a sodium alginate solution prepared with 2.1 parts of sodium alginate to granulate. Then place them in a calcium chloride solution prepared with 3.0 parts of calcium chloride for crosslinking for 45 minutes. After filtration, dry them at 35°C for 9 hours to obtain nutrient slow-release granules. Step 4: Weigh 370 parts of cement, 55 parts of fly ash, 45 parts of mineral powder, 670 parts of fine aggregate and 1090 parts of coarse aggregate and add them to the concrete mixer. Dry mix for 100 seconds to obtain a dry-mixed aggregate system. Step 5: Mix 160 parts of water and 5.5 parts of water-reducing agent and add them to the dry aggregate system. Stir for 130 seconds to obtain the basic concrete mixture. Step 6: Add 34 parts of microbial mineralization repair particles and 22 parts of nutrient slow-release particles to the base concrete mixture, and stir at low speed for 100 seconds to make the microbial mineralization repair particles and nutrient slow-release particles evenly dispersed, and obtain microbial self-healing crack concrete mixture. Step 7: Pour the microbial self-healing crack concrete mixture into the mold, vibrate it for 70 seconds, smooth the surface, cover it with a film, remove it from the mold after 24 hours, and place it in a standard curing environment of 20℃ and 95% relative humidity for 28 days to obtain microbial self-healing crack concrete.

[0031] Regarding parameter adjustments: In step 6, the addition amounts of microbial mineralization repair particles and nutrient slow-release particles are used to regulate crack repair efficiency and concrete mechanical properties. When the addition amount of microbial mineralization repair particles is less than 22 parts, the number of microorganisms that can be released in the crack area is insufficient; when the addition amount of microbial mineralization repair particles is greater than 34 parts, the number of weak interfaces inside the concrete increases, and the compressive strength decreases. In step 3, the ratio of calcium lactate to urea is used to regulate the calcium carbonate deposition rate. When the addition amount of urea is insufficient, the carbonate generation rate is low; when the addition amount of urea is too high, the local alkalinity increases too quickly, which is not conducive to the uniform deposition of calcium carbonate in the crack.

[0032] Example 4: This example provides a microbial self-healing crack concrete, which includes the following raw materials by weight: 365 parts cement, 60 parts fly ash, 42 parts mineral powder, 675 parts fine aggregate, 1085 parts coarse aggregate, 158 parts water, 5.2 parts water-reducing agent, 30 parts microbial mineralization repair particles, and 20 parts nutrient slow-release particles. The microbial mineralization remediation particles comprise the following raw materials in parts by weight: 21 parts of lightweight porous carrier, 38 parts of Bacillus pasteurellium bacterial solution, 2.2 parts of sodium alginate, 3.2 parts of calcium chloride, and 1.6 parts of protective agent; The sustained-release nutrient granules comprise the following raw materials in parts by weight: 26 parts calcium lactate, 13 parts urea, 4.5 parts sodium silicate, 2.0 parts sodium alginate, and 2.8 parts calcium chloride; The preparation method of the microbial self-healing crack concrete is as follows: Step 1: Weigh 21 parts of lightweight porous carrier, dry at 105℃ for 4 hours, cool to room temperature and place in a vacuum impregnation tank, add 38 parts of Pasteurella multocida bacterial solution and 1.6 parts of protectant, impregnate at -0.08MPa vacuum for 35 minutes, release the vacuum and let stand for 65 minutes to obtain bacteria-loaded porous particles. Step 2: Weigh 2.2 parts of sodium alginate and add it to deionized water and stir to dissolve, so as to obtain sodium alginate solution; add the bacteria-loaded porous particles to the sodium alginate solution and roll to coat for 22 min, then add them dropwise to a calcium chloride solution prepared with 3.2 parts of calcium chloride for cross-linking for 32 min, filter and dry at low temperature at 30℃ for 7 h to obtain microbial mineralization repair particles. Step 3: Weigh 26 parts of calcium lactate, 13 parts of urea and 4.5 parts of sodium silicate and mix them evenly. Add them to a sodium alginate solution prepared with 2.0 parts of sodium alginate to granulate. Then place them in a calcium chloride solution prepared with 2.8 parts of calcium chloride for crosslinking for 42 minutes. After filtration, dry them at 35°C for 9 hours to obtain nutrient slow-release granules. Step 4: Weigh 365 parts of cement, 60 parts of fly ash, 42 parts of mineral powder, 675 parts of fine aggregate and 1085 parts of coarse aggregate and add them to the concrete mixer. Dry mix for 100 seconds to obtain a dry-mixed aggregate system. Step 5: Mix 158 parts of water and 5.2 parts of water-reducing agent and add them to the dry aggregate system. Stir for 130 seconds to obtain the basic concrete mixture. Step 6: Add 30 parts of microbial mineralization repair particles and 20 parts of nutrient slow-release particles to the base concrete mixture, and stir at low speed for 95 seconds to obtain microbial self-healing crack concrete mixture. Step 7: Pour the microbial self-healing crack concrete mixture into the mold, vibrate it for 65 seconds, smooth the surface, cover it with a film, remove it from the mold after 24 hours, and place it in a standard curing environment of 20℃ and 95% relative humidity for 28 days to obtain microbial self-healing crack concrete.

[0033] The difference between Comparative Example 1 and Example 1 is that no microbial mineralization repair particles were added; the rest of the parts are the same as in Example 1. The difference between Comparative Example 2 and Example 1 is that no nutrient slow-release particles were added, while the rest of the parts are the same as in Example 1. The difference between Comparative Example 3 and Example 1 is that the porous particles carrying bacteria were not cross-linked with sodium alginate and calcium chloride, while the rest of the parts were the same as in Example 1. Comparative Example 4 uses ordinary C40 concrete.

[0034] Crack self-healing performance test: After standard curing for 28 days, concrete specimens prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to artificial cracks with a width of 0.30-0.60 mm by splitting loading. The initial crack width was recorded. The specimens were then placed in a wet curing environment with a temperature of 20℃ and a relative humidity of 95% for 28 days. The width of the repaired crack was recorded using a microscope, and the crack repair rate was calculated. The results are shown in Table 1.

[0035] The formula for calculating the crack repair rate is as follows: In the formula, H is the crack repair rate; This represents the initial crack width; This represents the width of the crack after repair.

[0036] Compressive strength recovery performance test: After the concrete specimens prepared in Examples 1-4 and Comparative Examples 1-4 were cured for 28 days, the compressive strength of the uncracked specimens was first measured. Then, the specimens in the same batch were pre-cracked and wet-cured for 28 days. The compressive strength of the repaired specimens was measured and the compressive strength recovery rate was calculated. The results are shown in Table 1.

[0037] The formula for calculating the compressive strength recovery rate is as follows: In the formula, The compressive strength recovery rate; The compressive strength of the repaired specimen; This represents the compressive strength of the uncracked specimen.

[0038] Permeability test: The concrete specimens prepared in Examples 1-4 and Comparative Examples 1-4 were pre-cracked and then wet-cured for 28 days. The permeability test was carried out according to the concrete permeability test method, and the maximum permeation height was recorded. The results are shown in Table 1.

[0039] Freeze-thaw cycle performance test: The concrete specimens prepared in Examples 1-4 and Comparative Examples 1-4 were pre-cracked and wet-cured for 28 days before being subjected to freeze-thaw cycle tests. The mass loss rate and relative dynamic elastic modulus were recorded after 100 freeze-thaw cycles. The results are shown in Table 1.

[0040] Table 1. Performance test results of microbial self-healing cracked concrete.

[0041] Table 1 shows that, compared with Comparative Examples 1-4, the microbial self-healing crack concrete prepared in Examples 1-4 has a higher crack repair rate, compressive strength recovery rate and relative dynamic elastic modulus, while having a lower maximum seepage height and freeze-thaw mass loss rate. This indicates that microbial mineralization repair particles and nutrient slow-release particles can synergistically improve the self-healing effect, impermeability and freeze-thaw durability of concrete cracks.

[0042] In Comparative Example 1, no microbial mineralization repair particles were added. The crack area lacked Bacillus pasteurellii, which can induce calcium carbonate deposition. The crack was mainly sealed by the continued hydration of unhydrated cement particles and the natural deposition of a small amount of carbonate. Therefore, the crack repair rate and compressive strength recovery rate were significantly reduced. In Examples 1-4, the microbial mineralization repair particles gradually released Bacillus pasteurellii after water entered the crack. Bacillus pasteurellii promoted the decomposition of urea and generated carbonate ions through the action of urease. The carbonate ions combined with calcium ions to form calcium carbonate deposition, thereby sealing the crack channel.

[0043] In Comparative Example 2, without the addition of slow-release nutrient particles, although Bacillus pasteurellii was present in the crack area, the lack of a continuously released calcium source and urea resulted in insufficient substrate for the microbial mineralization reaction, leading to a decrease in calcium carbonate deposition. Examples 1-4 provided calcium lactate and urea through slow-release nutrient particles, enabling continuous formation of calcium carbonate deposits during the wet cultivation stage of the cracks, improving the degree of crack closure and reducing the connectivity of seepage channels.

[0044] In Comparative Example 3, the porous particles carrying bacteria were not cross-coated with sodium alginate and calcium chloride. The survival rate of *Bacillus pasteurellii* decreased under the strong alkaline environment and mixing shear stress of concrete, and the bacteria were released too early, resulting in insufficient effective bacterial counts after crack formation. Examples 1-4, by cross-coating with sodium alginate and calcium chloride to form a gel protective layer, improved the survival rate of bacteria during mixing and hardening, and enabled responsive release after water ingress into cracks.

[0045] The microbial self-healing crack concrete prepared in Example 3 has superior comprehensive performance. This is because the 34 parts of microbial mineralization repair particles and 22 parts of nutrient slow-release particles can provide sufficient bacteria, calcium source and urea. The gel coating layer formed by 2.4 parts of sodium alginate and 3.5 parts of calcium chloride has good continuity, which can protect the bacteria in the strong alkaline environment of concrete and release them after water enters the crack, so that calcium carbonate is fully deposited in the crack, thereby improving the crack repair rate, compressive strength recovery rate, impermeability and freeze-thaw durability.

[0046] In the microbial self-healing cracked concrete and its preparation method of the present invention, Bacillus pasteurellii is loaded onto a lightweight porous carrier, and microbial mineralization repair particles are formed by cross-linking and coating with sodium alginate and calcium chloride. Nutrient slow-release particles are made by using calcium lactate, urea and sodium silicate. When cracks appear in the concrete and water enters, the microbial mineralization repair particles and nutrient slow-release particles gradually release bacteria, calcium source and urea in the crack area, which promotes the formation of calcium carbonate deposits in the crack, thereby achieving crack sealing, strength restoration and durability improvement.

Claims

1. A type of microbial self-healing cracked concrete, characterized in that, The microbial self-healing crack concrete comprises the following raw materials in parts by weight: 350-370 parts cement, 55-70 parts fly ash, 35-45 parts mineral powder, 670-690 parts fine aggregate, 1070-1090 parts coarse aggregate, 150-160 parts water, 4.5-5.5 parts water-reducing agent, 22-34 parts microbial mineralization repair particles, and 14-22 parts nutrient slow-release particles; The microbial mineralization remediation particles include a lightweight porous carrier, Bacillus pasteurellium culture, sodium alginate, calcium chloride, and a protective agent. The sustained-release nutrient granules include calcium lactate, urea, sodium silicate, sodium alginate, and calcium chloride.

2. The microbial self-healing cracked concrete according to claim 1, characterized in that: The microbial mineralization remediation particles comprise the following raw materials in parts by weight: 18-22 parts of lightweight porous carrier, 30-40 parts of Bacillus pasteurellium bacterial solution, 1.6-2.4 parts of sodium alginate, 2.5-3.5 parts of calcium chloride, and 1.2-1.8 parts of protective agent.

3. The microbial self-healing cracked concrete according to claim 2, characterized in that: The sustained-release nutrient granules comprise the following raw materials in parts by weight: 22-28 parts calcium lactate, 10-14 parts urea, 3-5 parts sodium silicate, 1.5-2.1 parts sodium alginate, and 2.0-3.0 parts calcium chloride.

4. The microbial self-healing cracked concrete according to claim 3, characterized in that: The cement is P.O42.5 ordinary Portland cement; the fly ash is Grade II fly ash; the mineral powder is S95 grade granulated blast furnace slag powder; the fine aggregate is river sand with a fineness modulus of 2.6; the coarse aggregate is continuously graded crushed stone with a particle size of 5-20mm; and the water-reducing agent is polycarboxylate high-efficiency water-reducing agent with a water reduction rate ≥25%.

5. The microbial self-healing cracked concrete according to claim 4, characterized in that: The lightweight porous carrier is one of expanded perlite, zeolite powder, and ceramsite powder; the concentration of the Bacillus pasteurellium inoculum solution is [missing information]. The protective agent is made by mixing trehalose and skim milk powder in a mass ratio of 1:

1.

6. A method for preparing microbial self-healing crack concrete according to any one of claims 1-5, characterized in that, Specifically, the steps include the following: Step 1: Weigh a lightweight porous carrier and dry it. After cooling to room temperature, place it in a vacuum impregnation tank, add Bacillus pasteurellium bacterial solution and protectant, remove the vacuum after vacuum impregnation and let it stand to obtain bacteria-loaded porous particles. Step 2: Weigh sodium alginate and add it to deionized water and stir to dissolve it to obtain sodium alginate solution. Add the bacteria-loaded porous particles to the sodium alginate solution and roll them to coat them. Then add them dropwise to calcium chloride solution for cross-linking. After filtration, dry them at low temperature to obtain microbial mineralization repair particles. Step 3: Weigh calcium lactate, urea and sodium silicate, mix them evenly, add them to sodium alginate solution to granulate, then place them in calcium chloride solution for cross-linking, filter and dry to obtain nutrient slow-release granules; Step 4: Weigh out cement, fly ash, mineral powder, fine aggregate and coarse aggregate and add them to a concrete mixer to dry mix and obtain a dry-mixed aggregate system; Step 5: Mix water and water-reducing agent and then add to the dry aggregate system and stir to obtain the basic concrete mixture; Step 6: Add the microbial mineralization repair particles and nutrient slow-release particles to the base concrete mixture and stir at low speed to obtain the microbial self-healing crack concrete mixture. Step 7: Pour the microbial self-healing crack concrete mixture into the mold, vibrate it, smooth the surface, cover it with a film, demold it, and cure it according to standard to obtain microbial self-healing crack concrete.

7. The method for preparing microbial self-healing crack concrete according to claim 6, characterized in that: In step 1, the drying temperature of the lightweight porous carrier is 105℃ and the drying time is 4h; the vacuum degree of the vacuum impregnation is -0.075MPa to -0.085MPa, the vacuum impregnation time is 25-40min, and the standing time after the vacuum is released is 50-70min.

8. The method for preparing microbial self-healing crack concrete according to claim 7, characterized in that: In step 2, the rolling coating time is 18-25 min, the crosslinking time is 25-35 min, the low-temperature drying temperature is 30℃, and the low-temperature drying time is 6-7 h; In step 3, the crosslinking time is 35-45 min, the drying temperature is 35℃, and the drying time is 8-9 h.

9. The method for preparing microbial self-healing crack concrete according to claim 8, characterized in that: In step 4, the dry mixing time is 90-100 seconds; In step 5, the stirring time is 120-130 seconds; In step 6, the low-speed stirring time is 80-100s.

10. The method for preparing microbial self-healing crack concrete according to claim 9, characterized in that: In step 7, the compaction time is 60-70 seconds, the demolding time is 24 hours, the standard curing temperature is 20°C, the relative humidity is 95%, and the standard curing time is 28 days.